2013
DOI: 10.2478/amm-2013-0174
|View full text |Cite
|
Sign up to set email alerts
|

Some Structural Aspects of Ionic Conductivity in Co-Doped Ceria-Based Electrolytes

Abstract: The sinters of co-doped ceria solid solutions with the formula of Ce 0.85 Sm 0.15−x R x O 1.9 , where R = Y, Gd, Pr, Tb, 0 0.05 into solid solution Ce 0.85 Sm 0.15−x R x O 1.9 , R = Tb, Pr caused a decrease in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…are summarized in Table . The values of E act (1.04‐1.21 eV) obtained in the region I are in correspondence with ionic conductivity, usually observed at high temperature in dielectric materials such as ZrO 2 ‐Y 2 O 3 , CeO 2 :Y 2 O 3 and LaBi 5 Fe 2 Ti 3 O 18 . In perovskite‐type oxides, such as SrTiO 3 ceramics, activation energies 1.02‐1.08 eV have been ascribed to oxygen vacancy mobility in concordance with values reported in the region I of the present study.…”
Section: Resultssupporting
confidence: 91%
“…are summarized in Table . The values of E act (1.04‐1.21 eV) obtained in the region I are in correspondence with ionic conductivity, usually observed at high temperature in dielectric materials such as ZrO 2 ‐Y 2 O 3 , CeO 2 :Y 2 O 3 and LaBi 5 Fe 2 Ti 3 O 18 . In perovskite‐type oxides, such as SrTiO 3 ceramics, activation energies 1.02‐1.08 eV have been ascribed to oxygen vacancy mobility in concordance with values reported in the region I of the present study.…”
Section: Resultssupporting
confidence: 91%
“…A study has shown that doped ceria-based electrolytes exhibit electronic conductivity mainly at high temperatures (>1000°C) [3]. Moreover, the oxide ion transference number of co-doped ceria electrolytes is close to 1 [23,24]. Therefore, the conductivity obtained from Eq.…”
Section: Electrical Propertiesmentioning
confidence: 98%